Recirculated system design for eco-burner based on intake manifold in reciprocating engine - Faiz, Bin Othman (Universiti Malaysia Sarawak (UNIMAS), 2017)
An eco-burner, also known as furnace, is a device used for high-temperature heating. Operating 24 hours a day, and 365 days a year, efficiency of the system plays an important role in the desired process and power consumption. There are many factors that leads to inefficiency of furnace operation, such as waste-gas losses, fuel-air ratios, air infiltration, and furnace scheduling and loading. Hence a properly designed system of furnace will help to eliminate the effects that will be caused by these factors. In order to increase the combustion efficiency, which is to deliver a higher value of heat output, a recirculation air system was designed and simulated. The objective is to design ?>an optimum air flow system in a furnace and to improve local charcoal production industry. Also, the result was compared to the non-recirculated air system. The design process of the models and analysis of air combustion movement is determined by computational fluid dynamics simulation software, Ansys Workbench. From the results obtained using the simulation, the recirculation air system gives an outlet temperature of 800°C, while the non-recirculated air system provides an outlet temperature of 591°C. It shows that recirculation of air provide more heat compared to the non-recirculated air system by 19.5%, with same power usage, hence more efficient and cost-effective enabling optimal and stable charcoal production all year round.